2020
DOI: 10.1186/s12864-020-07153-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, and phylogenetic and expression profiling analyses, of XTH gene families in Brassica rapa L. and Brassica oleracea L.

Abstract: Background Xyloglucan endotransglucosylase/hydrolase genes (XTHs) are a multigene family and play key roles in regulating cell wall extensibility in plant growth and development. Brassica rapa and Brassica oleracea contain XTHs, but detailed identification and characterization of the XTH family in these species, and analysis of their tissue expression profiles, have not previously been carried out. Results In this study, 53 and 38 XT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 78 publications
(84 reference statements)
6
18
1
Order By: Relevance
“…XET_C contained the motif 5 and motif 10. This results were similar to the previous study (Wu et al 2020).…”
Section: Gene Structure Analysis Of Poplar Xth Family Genessupporting
confidence: 94%
See 1 more Smart Citation
“…XET_C contained the motif 5 and motif 10. This results were similar to the previous study (Wu et al 2020).…”
Section: Gene Structure Analysis Of Poplar Xth Family Genessupporting
confidence: 94%
“…As shown in the Fig. 1, the evolutionary tree could be divided into 4 groups (Group / , Group A, Group B and Early diverging group), which was similar to Brassica rapa (Wu et al 2020). We found that the Group / contained the most members with 33 members.…”
Section: Identi Cation and Phylogenetic Of Xth Family Genesmentioning
confidence: 60%
“…As shown in the Fig. 1 , the XTH family could be divided into 4 groups (GroupI/II, Group IIIA, Group IIIB and Early diverging group), which was similar to that in Brassica rapa [ 9 ]. And the GroupI/IIcontained the most members with 33 members.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, a small part of outlier group (early diverting) was found in detailed clade [ 7 , 8 ]. In summary, XTH family is divided into I / II, IIIA, IIIB and the early diverting groups [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 ). Studies showed that the expression of AtXTH5 was also significantly upregulated under Al stress [ 31 ]. The expression levels of CsXTH 5 and CsXTH13 decreased when Al 3+ concentration increased to 4 mM (Fig.…”
Section: Discussionmentioning
confidence: 99%